PENERAPAN PROBLEM BASED LEARNING PADA PEMBELAJARAN TEMATIK UNTUK MENINGKATKAN KEMAMPUAN MEMECAHKAN MASALAH SISWA SD - Tiara (ADISAM PUBLISHER, 2026)
This study aims to examine the implementation of the Problem Based Learning (PBL) model in thematic learning to improve elementary school students’ problem-solving skills. The background of this research is based on the low ability of students to understand and solve problems related to their daily lives. Teacher-centered learning processes tend to make students less active and less trained in critical thinking. This research employs a quantitative approach using a simple experimental method. The subjects of the study were elementary school students participating in thematic learning. Data were collected through problem-solving tests, observations, and documentation. The results show that the implementation of the PBL model significantly improves students’ problem-solving abilities. Students become more active in the learning process, are able to collaborate better, and show greater confidence in expressing their ideas and finding solutions. In conclusion, the Problem Based Learning model is effective in thematic learning to enhance problem-solving skills among elementary school students.